2013
DOI: 10.1007/s10903-012-9757-5
|View full text |Cite
|
Sign up to set email alerts
|

“Judging a Body by Its Cover”: Young Lebanese-Canadian Women’s Discursive Constructions of the “Healthy” Body and “Health” Practices

Abstract: Our interest stems from the dramatic increase in the number of obesity studies, which expose Canadian women to a huge amount of information that links health to weight. Using feminist poststructuralist and postcolonial lenses, this paper investigates young Lebanese-Canadian women's constructions of the body and "health" practices within the context of the dominant obesity discourse. Participant-centered conversations were held with 20 young Christian Lebanese-Canadian women. A thematic analysis was first condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Some participants decentered healthist messages in media accounts of food celebrities to focus on broader (non-health) understandings of the self. Furthermore, similar to results in studies on obesity discourse in racially marginalized groups (Abou-Rizk & Rail, 2014; McPhail, 2013), these African American Kentuckians created “micro-resistances” to the dominant neoliberal discourse about health. Participants questioned the authority of government food programs, obtained but did not use health-promoting information from media accounts and physicians, and reinterpreted the consumption of traditional foods as “healthy” when consumed occasionally.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Some participants decentered healthist messages in media accounts of food celebrities to focus on broader (non-health) understandings of the self. Furthermore, similar to results in studies on obesity discourse in racially marginalized groups (Abou-Rizk & Rail, 2014; McPhail, 2013), these African American Kentuckians created “micro-resistances” to the dominant neoliberal discourse about health. Participants questioned the authority of government food programs, obtained but did not use health-promoting information from media accounts and physicians, and reinterpreted the consumption of traditional foods as “healthy” when consumed occasionally.…”
Section: Discussionsupporting
confidence: 59%
“…Results from this article have additional implications for the ongoing study of healthicization in Black communities. First, unlike much of the previous healthicization research in which individual choice is constrained by social expectations to engage in explicit and conscious regimens of health-promoting behaviors, this article supports emergent research showing that marginalized communities exercise agency (Abou-Rizk & Rail, 2014; McPhail, 2013). In this article, we drew upon Armstrong and Murphy’s work (2012) that formulated resistance as a multi-dimensional and nuanced concept, including not only overt contestation or non-acceptance of healthist messages but also more subtle acts of resistance.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…26 In a study of 20 Lebanese-Canadian young women, women described a healthy body as a thin body and stated that they often went on diets and used methods such as herbal methods, detox practices, and slimming pills to achieve this image. 27 Detox diets are popular types of diets which often lead to excessively low-calorie intake in a short time. Weight gain is possible following detox diets when a normal diet is restarted, and long-term sustainability may not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that young people tried to change their bodies to achieve the perceived ideal body 26 . In a study of 20 Lebanese‐Canadian young women, women described a healthy body as a thin body and stated that they often went on diets and used methods such as herbal methods, detox practices, and slimming pills to achieve this image 27 . Detox diets are popular types of diets which often lead to excessively low‐calorie intake in a short time.…”
Section: Discussionmentioning
confidence: 99%